182k views
1 vote
Write the expression in simplest form.
( 4 = + 3) – 2(- \ - - })= 0

User SimaWB
by
5.1k points

1 Answer

4 votes

Answer:

3^x=9^{x+5}

Explanation:

3^x=9^{x+5}

x^2-x-6=0

x^4-5x^2+4=0

\sqrt{x-1}-x=-7

\left|3x+1\right|=4

\log _2\left(x+1\right)=\log _3\left(27\right)

3^x=9^{x+5}

If request to solve;

\mathrm{Convert\:}9^{x+5}\mathrm{\:to\:base\:}3

9^{x+5}=\left(3^2\right)^{x+5}

\mathrm{Solve\:}\:x=2\left(x+5\right):\quad x=-10

User Trevan Hetzel
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.